"Be careful what you recall": Retrieval-induced forgetting of genuine real-life autobiographical memories. Issue 1 (January 2023) - Somos, Eszter; Mazzoni, Giuliana; Gatti, Daniele; Jellema, Tjeerd
Which episodes from our lives will be remembered and which will be forgotten, and why? This question has still not been answered satisfactorily by research into autobiographical memory. Previous work has shown that retrieval-induced forgetting (RIF) might be a factor responsible for forgetting parts of the autobiographical memory content. However, none of the previous studies assessed RIF in memories for recent, controlled, personal events. We report here the results of an experiment in which autobiographical memories of real-life events were induced in a controlled, but fully naturalistic, manner under the disguise of team-building exercises, while an adapted RIF paradigm was applied to these memories. Results clearly showed the influence of RIF on autobiographical memory retrieval. These findings demonstrate conclusively that RIF occurs in everyday life when remembering personal events.